(The isolation of beta-carotene component from crude palm oil using absorption method) - Sudibyo, agus; -, Suprapto (Balai Besar Industri Agro, 1993)
This report deals with a study on the effect of bleaching earth type used and methods of adding the bleaching earth on the isolation of beta-carotene content from crude palm oil (CPO) using absorption method.The type of bleaching earth used were Master Brand,Champion and Bentonit alam Indonesia,while the bleaching earth concentration used was 15% which given in three methods i.e.first it was given at once addition only, second at twice addition and third at three times addition.It was shown that the combination treatment between Bentonit Alam Indonesia bleaching earth,gave the best result with 55,08% beta-carotene content,11.00% loss quantity of crude palm oil and 55 ppm beta caronete content of crude palm oil after bleaching process.